Duodenal chemosensing. Issue 6 (November 2018) - Iwasaki, Mari; Akiba, Yasutada; Kaunitz, Jonathan D.
Abstract : Purpose of review: Luminal chemosensing is a term used to describe how small molecules in the gut lumen interact with the host through surface receptors or via transport into the submucosa. In this review, we have summarized recent advances of understanding luminal chemosensing in the gastroduodenal mucosa, with a particular emphasis on how chemosensing affects mucosal protective responses and the metabolic syndrome. Recent findings: In the past decade, data have supported the hypothesis that gut luminal chemosensing not only is important for the local or remote regulation of gut function but also contributes to the systemic regulation of metabolism, energy balance and food intake. We have provided examples of how luminal nutrients such as long-chain fatty acids (LCFAs), endogenous compounds such as bile acids, bacterial metabolites such as short-chain fatty acids (SCFAs) and bacterial components such as lipopolysaccharide (LPS) activate cognate receptors expressed on key effector cells such as enteroendocrine cells and inflammatory cells in order to profoundly affect organ function through the initiation or suppression of inflammatory pathways, altering gut barrier function and nutrient uptake, altering gut motility and visceral pain pathways, and preventing mucosal injury. Summary: These recent discoveries in this area have provided new possibilities for identifying novel molecular targets for the treatment of mucosal injury, metabolic disorders and abnormal visceral sensation. Understanding luminal chemosensory mechanisms may help to identify novel molecular targets for the treatment and prevention of mucosal injury, metabolic disorders and abnormal visceral sensation.